PROFIL HORMON ESTROGEN DAN PROGESTERON PADA SIKLUS BERAHI KAMBING LOKAL (Estrogen and Progesterone Profile in Aceh Local Goat Estrous Cycle ) - Tongku Nizwan Siregar (Universitas Syiah Kuala, 2009)
The aim of this research was to find out the normal estrogen and progesterone profile in local goat estrous cycle. Five female Aceh local goats which the criteria clinically in good condition, have been giving birth before, 1.5-3.0 years old, and showed minimal twice regularly estrous cycle. All samples were synchronized with 0.5 ml cloprostenol (Estrone, Bioveta) using randomly infection pattern. The data obtained were analyzed descriptively. Blood serum was collected for examination of estrogen and progesterone content on 0, 7, 14, and 21 day of estrous cycle (day 0 of estrous cycle). Hormone analysis was conducted using ELISA. The results showed that estrogen and progesterone profile on day 0, 7, 14, and 21 were 62.21; 28.61; 29.84; 79.89 pg/ml and 0.0; 8.6; 14.7; 0.0 ng/ml respectively.Keywords: estrogen, progesterone, estrous cycle, Aceh local goats